Dynamic connection provisioning in fiber-wireless access networks using tuning-based roadms - Anyuo, Shadrack Omondi (2012)
Dissertação de mest., Ciências de Computação, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2010